Experimental study on methane hydrate formation in a partially saturated sandstone using low-field NMR technique. (1st September 2019) - Ji, Yunkai; Hou, Jian; Cui, Guodong; Lu, Nu; Zhao, Ermeng; Liu, Yueliang; Du, Qingjun
Highlights: Methane hydrate formation was studied by low-field NMR technology under formation conditions. The spatial distribution of methane hydrate is heterogeneous. The mechanism of methane hydrate formation in small pores is different from that in large pores. Methane hydrate tends to form in the pore center of sandstone. Abstract: Kinetics of hydrate formation in the porous media is important for carbon storage and the feasibility assessment of developing natural gas hydrates. In this study, we used a novel and real-time monitoring apparatus which combined the hydrate formation system with the low-field nuclear magnetic resonance measurement system to study on the characteristics of methane hydrate formation in a partially saturated sandstone. Results show that hydrate coexists with water and methane in the sandstone at the end of methane hydrate formation by an excess-gas method. Magnetic resonance imaging shows that the spatial distribution of hydrate is affected by the initial distribution of water in the sandstone. Water content plays a role in controlling the termination of hydrate formation. Based on the transverse relaxation time distribution analysis, free gas exists mainly in the large pores, while methane molecules can enter the small pores by dissolution and diffusion, forming methane hydrate with water molecules in the absence of free gas. Methane hydrate is formed in the center of both large and small pores by the excess-gas method. The rate of methane hydrate formation is slower in the small pores than that in the large pores. The range of pore size gradually decreases with the hydrate formation.